Pemberian Aromaterapi Lavender terhadap Kualitas Tidur Pasien Hemodialisis - Hartati, Yeni; Nursanti, Irna; Irawati, Diana; Natashia, Dhea; Hasanah, Uswatun (Journal of Telenursing (JOTING), 2023)
This study aims to determine the effectiveness of lavender aromatherapy on hemodialysis patients' sleep quality. The method used is experimental intervention twice a week for four weeks. Before and after the intervention, sleep quality will be measured using the PSQI (Pittsburgh Sleep Quality Index) instrument. The results showed that (t = 22.789, p = 0.0001). 7.3% of the variable variation in the model was able to explain changes in the percentage of sleep quality (R2=0.073). Education variables (β=0.240, p=1.888), duration of HD (β=0.227, p=1.583), and the variable that is a predictor of sleep quality is gender (β=-0.006, p=0.421). In conclusion, there is a relationship between giving lavender aromatherapy and the sleep quality of hemodialysis patients compared to patients who did not receive lavender aromatherapy. Keywords: Lavender Aromatherapy, Hemodialysis, Sleep Quality